Correction to: Application of Mathematical Modelling as a Tool to Analyze the EEG Signals in Rat Model of Focal Cerebral Ischemia (Journal of The Institution of Engineers (India): Series B, (2014), 95, 1, (23-27), 10.1007/s40031-014-0072-5) - Paul, S.; Bhattacharya, P.; Pandey, A.K.; Patnaik, R. (Springer, 2020)
In the original publication of the article, figure 1 was published incorrectly. The corrected figure is given below. © 2020, The Institution of Engineers (India).
Keywords: Application of Mathematical Modelling; Analyze the EEG Signals; Rat Model of Focal Cerebral Ischemia